Optimalisasi Penggunaan Terapi Akupuntur dalam Menurunkan Tekanan Darah pada Penderita Hipertensi - Ida Ayu Suptika Strisanti; Ida Ayu Anom Rastiti; Kadek Buja Harditya; I Dewa Ayu Agra Darmawati; Komang Rosa Tri Anggaraeni; Ni Wayan Kesari Darmapatni; I Gede Suweca (Poltekkes Kemenkes Kupang, 2026)
Background: Hypertension is a major non-communicable disease that leading a highest risk into morbidity and mortality due to cardiovascular complications. Although acupuncture has been utilized in the management of hypertension, the existing scientific evidence remains variable and inconsistent. Objectives: Therefore, further research is warranted to address this gap, particularly in evaluating the effectiveness of acupuncture in a measurable and evidence-based manner for reducing blood pressure. Methods: The pre-experimental with a one-group pretest-posttest was used as a design in this study. A total of 40 hypertensive patients were recruited using accidental sampling method. Acupuncture was administered for 30 minutes using Taichong (LR3), Neiguan (PC6), Hegu (LI4), Shenmen (HT7), and Sanyinjiao (SP6) points. Blood pressure measurements were taken pre and post intervention and the data was analyzed by Wilcoxon Signed Rank Test. Results: There was a reduction from Md=152 mmHg to Md=140 mmHg in systolic pressure and Md=93 mmHg to Md=84 mmHg for diastolic after the intervention. Statistical analysis revealed a significant difference with p < 0.001 (Z = 4.7; r = 0.52), indicating that acupuncture therapy has a moderate to strong effect in reducing blood pressure. Conclusions: Acupuncture is effective as a complementary therapy in reducing blood pressure among hypertensive patients. The integration of acupuncture into healthcare services may serve as a strategic alternative to improve hypertension management.